Proprietary Land Registration Policy is Based on Government Regulation Number 18 of 2021 Concerning Land Registration Rights - Fadila Fais Alim; Moh. Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Population growth is increasing every year, in proportion to the need for land. This shows that soil is an important element for humans. Land is an important economic factor and has strategic value wherever it is social, political or cultural. This imbalance forces people to use various methods to dominate and even own land, although in the end it will lead to disputes, conflicts and land issues. To ensure legal certainty of land rights, land registration activities are carried out which are a series of land administration activities in collecting and processing physical and juridical data. The research approach method used by researchers is empirical juridical by using approach/theory/concept and analytical methods which are included in the dogmatic discipline of Law. This study aims to study the legal basis used in land registration and to study the mechanism of land registration in Indonesia. This research conducts research related to the Policy of Land Registration Based on Property Rights Peraturan Pemerintah Nomor 18 Tahun 2021 Tentang Hak Pendaftaran Tanah in BPN Pati. The findings of this study indicate that the land registration policy in Indonesia refers to Undang-Undang No. 5 tahun 1960 tentang peraturan dasar pokok-pokok agraria where in its development there is an adjustment with the release PP No. 18 Tahun 2021 tentang Hak Pengelolaan, Hak Atas Tanah, Satuan Rumah Susun dan Pendaftaran Tanah.